Identitas arsitektur Kota Banjarmasin: Pola struktur kota sungai pasang surut dan tipologi bangunannya - Yohanes Karyadi Kusliansjah (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
Banjarmasin, known as the city of a thousand rivers, is an accumulation of multi-deltas sedimentation, located -0.16 meters below sea level and 23 km from the estuary of the Barito river. The city embryo, which acts as the western boundary between the Martapura river and tributary regions, is influenced by daily tides from the Java sea. The morphological structure and building typology formation of tidal hydrodynamics influence the characteristic of the environmental context identity. Furthermore, the life adaptation to the natural context identity is a unique traditional water-based culture on the physical, territorial, and cultural order, characterized by the physical, functional, and normative attributes from the pre-colonial to the colonial era. Therefore, this study aims to identify the architectural identity of Banjarmasin's tidal river city and its forming elements through a morpho-typological approach using an interpretive-descriptive-retrospective method. The results showed that the structural identity of the architecture of Banjarmasin environment, as a tidal river city, is fragmented in the form of many deltas, thereby leading to sedimentation from river tributary in dendritic and meander patterns. In conclusion, the people's life adaptation to the natural environment created a traditional water culture with four contextual building typologies of the tidal river, namely raft, water stilt, land stilt, and landed houses with underground reservoir.